SISTEM MANAJEMEN PEMESANAN ROKOK SOSROBAHU BERBASIS WEBSITE MULTI-LEVEL USER (STUDI KASUS: CV SENTOSO JAYA TEMBAKAU) - Junia Vitasari; Adisty Pramudita Putri Rudi; Abdulloh Haidar Azzam Ash’shobir; Mochammad Enrique Lazuardi Ramadany (Lembaga Pengembangan Kinerja Dosen, 2025)
The rapid development of technology has driven digital transformation in various sectors, including the distribution of goods. Logistics digitization, particularly through the use of website-based systems, can improve operational efficiency and enhance company competitiveness. This research aims to develop a multi-level user website-based cigarette order management system at CV Sentoso Jaya Tembakau to address the issues of inefficient management of distribution data, such as accounts, prices, stocks, and transactions. The developed system integrates the ordering process, stock management, and real-time turnover monitoring, making cigarette distribution more structured and efficient. The results show that the system successfully improved operational efficiency and reduced the potential for errors in managing distribution data. With this system, CV Sentoso Jaya Tembakau can manage cigarette distribution more effectively and transparently.